The effect of Trypanosoma vivax infection on late pregnancy and post-partum return to cyclicity in Boran cattle - Okech, G.; Watson, E.D.; Luckins, A.G.; Makawiti, D.W. (OAU, 1995)
A study was designed to examine the effect of infection with Trypanosoma vivax KETRI 2501 on the maintenance of pregnancy and post-partum return to reproductive normality in susceptible Galana and trypanotolerant Orma Boran heifers during the third trimester of pregnancy. One out of three Galana heifers had a premature birth and subsequent perinatal mortality. Of the two heifers that produced live calves, one of the calves died shortly after birth, while the other survived. Two out of three Orma heifers had premature births, and all three calves died shortly after survived. Two out of three Orma heifers had premature births, and all three calves died shortly after birth. All control animals produced live calves at term, which all survived. Infection with T. vivax during the third trimester of pregnancy delayed the resumption of ovarian activity after calving, with the Ormas taking a significantly (P